HAS THE EVOLUTION OF HOMO SAPIENS DOMESTICATED METABOLIC DISEASES LIKE DIABETES? A NARRATIVE REVIEW - Shankar, Dr Anand; Choudhary, Pallawee; Shankar, Dr. Vikas; Shankar, Dr. Vivek; Sharma, Dr. Anisha; Shivhare, Dr. Arati; Dr. Mandavi; Mahule, Dr Aushili (Student's Journal of Health Research Africa, 2023)
In this narrative review article, we attempt to review the information available to support the possible link between the evolution of Homo sapiens and the increase in metabolic diseases like diabetes. The Ardipithecus group, which lived around 6 million years ago, is considered the earliest humans closely linked to primates. The taxonomic assemblage encompasses Orrorin tugenensis, Sahelanthropus tchadensis, Ardipithecus ramidus, and Ardipithecus kadabba. Australopithecus anamensis, the initial reported member of the Australopithecines, inhabited the Earth approximately 4.2 to 3.8 million years in the past, demonstrating a combination of characteristics similar to both apes and human beings. They were bipedal and had an ankle joint that allowed them to walk upright. Australopithecus afarensis, another member of the group, had apelike traits such as long arms with curved fingers but was also bipedal and had a small brain case. Their capability to walk standing and climb trees assisted them in surviving for nearly 900,000 years. Various studies have shown that food, BMI, habits, early puberty, use of pesticides, and environmental changes can all impact the incidence of diabetes. Domestication has allowed us (Homo Sapiens) to survive more efficiently, civilize more effectively and socialize more adequately. This natural course of evolution has taken and will continue to take millions of years. Future research and policy development may benefit from interdisciplinary approaches and a deeper exploration of the evolutionary aspects of human health.